MAPPING THE DISTRIBUTION OF MANGROVE FORESTS USING REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEMS IN THE DISTRICT OF BANGKALAN, EAST JAVA PROVINCE - Iqbal, Muhammad Nurdzat; Risjani, yenny (Journal of Food and Life Sciences, 2018)
This research is done in Bangkalan Coast, East Java Province in August - November 2009. This potential development area have been threaten by exploitation that can cause damage to the coastal environment and natural resources. In order to prevent damage and to protect the ecosystems in coastal region, mangrove forest conditions have to be monitored continuously. Remote sensing data such as Landsat ETM+ can generate information about the condition of mangrove forest, such as distribution, extent and canopy density rate. The objective of the research was to determine distribution and extent of  mangrove forest at Bangkalan Coast using remote sensing and geographic information systems. The research was done survey method with descriptive explanations of the primary data and secondary data. The research uses a combination of satellite image processing Landsat ETM+, field survey and thematic maps with manual analysis.The result from interpretation of image analysis showed that Bangkalan Coast has 46.66 hectares mangrove forest, with detailed information about density of the mangrove area is 37,89 hectare for very rare and 8,55 hectare for rarely density. The result for measuring environmental factors showed as follows: salinity ranged from 15‰ – 30 ‰ , the tide of single type (diurnal type) and the substrates is clay, clay loam and dust clay. Keywords: Mangrove, Remote Sensing, GIS